Design and Implementation of Pedestrian Flow Monitoring and Warning Platform in Public Area based on Pedestrian Detection. (August 2020) - Zhen, Aijun; Wang, Qingli; Wang, Ancheng; Wu, Kai
Abstract: In the traditional public area pedestrian flow monitoring, a lot of manpower and material resources are needed. Only relying on people's eyes to identify and count the number of people in the video under monitoring is not only inefficient, but also has errors in accuracy and wastes a certain amount of energy and financial resources. In the rapid development trend of artificial intelligence, this system starts from the perspective of real-time monitoring, with the maturity and development of machine vision technology, and creates a cloud monitoring platform based on JavaWeb technology. The pedestrian detection technology is applied to the pedestrian flow monitoring, which provides a feasible scheme for accurate and fast pedestrian flow monitoring and warning, and develops a system to help public area managers and government departments to deal with the crowd gathering situation, analyze and monitor the crowd density, and give a quick warning to the crowd outbreak and gathering place.